Optical enhancement of IBC solar cell using quokka 3D simulation - Sia, Albert Kah Dak, 1994-, author; Amirjan Nawabjan, 1986-, supervisor; Fakulti Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2018